2001
DOI: 10.1139/p01-010
|View full text |Cite
|
Sign up to set email alerts
|

Rate coefficients for rotationally inelastic collisions of CO with H2

Abstract: We have performed quantum-scattering calculations to determine inelastic rate coefficients of the astrophysically important collision system CO-H 2 . We have used a modified version of the most recent potential-energy surface by Jankowski and Szalewicz (J. Chem. Phys. 108, 3554 (1998)), which has been proven to be superior to a previous potential surface by comparison with experimental pressure broadening data. In contrast to previous studies we find that inelastic rates with J = 2 for CO are smaller than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
3
11
1
Order By: Relevance
“…The rate coefficients are large because the potential energy surface is highly anisotropic, although they are smaller than those from collisions with atomic hydrogen (Green & Thaddeus 1976;Balakrishnan et al 2001) for which the interaction potential has a deep well. They are comparable to those from collisions with ortho and para hydrogen (Flower 2001;Mengel, De Lucia, & Herbst 2001), some being larger and some being smaller.…”
Section: Tablesupporting
confidence: 54%
“…The rate coefficients are large because the potential energy surface is highly anisotropic, although they are smaller than those from collisions with atomic hydrogen (Green & Thaddeus 1976;Balakrishnan et al 2001) for which the interaction potential has a deep well. They are comparable to those from collisions with ortho and para hydrogen (Flower 2001;Mengel, De Lucia, & Herbst 2001), some being larger and some being smaller.…”
Section: Tablesupporting
confidence: 54%
“…Due to their astrophysical importance as H 2 and CO are the most abundant molecules in a broad spectrum of astrophysical objects, the H 2 -CO collisional system has been the subject of numerous experimental [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and theoretical [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] studies. Quantitative determinations of state-to-state cross sections and rate coefficients for H 2 -CO collisions are crucial to numerical astrophysical models.…”
Section: Introductionmentioning
confidence: 99%
“…Rate coefficients for collisions with H 2 based on the potential energy surface (PES) of Jankowski & Szalewicz (1998, hereafter JS98), have been calculated recently (Mengel et al 2001;Flower 2001). These rates were found to be in reasonable agreement (typically within a factor of 2 at 10 K) with those computed on older and less Tables A1 and A2 are only available in electronic form at http://www.edpsciences.org accurate PES (e.g.…”
Section: Introductionmentioning
confidence: 84%
“…A modification which consists of multiplying the PES by a factor of 0.93 was therefore suggested by these authors. This modification was applied by Mengel et al (2001) and it was indeed found to produce better agreement with measurements of pressure broadening cross sections. On the other hand, the original PES was found to give a very good agreement with experimental state-to-state rotational cross sections measured near 1000 cm −1 (Antonova et al 2000).…”
Section: Introductionmentioning
confidence: 94%